A Network Analysis of Control-Value Appraisals and Classroom-Related Enjoyment, Boredom, and Pride - David William Putwain; Martin Daumiller (MDPI AG, 2023)
Control-value theory (CVT) proposes that discrete emotions arise from combinations of control-value appraisals of learning activities and outcomes. Studies have supported this proposition using factor analytic and latent profile, analyses. Network analysis (NA), however, has not been widely used within the field of educational psychology or to investigate the propositions of CVT. In the present study we set out to examine how control-value appraisals related to three commonly experienced classroom emotions, enjoyment, boredom, and pride, using network analysis. In addition, we included positive and negative facets of value. The sample comprised 170 students (53.5% female) in their first year of secondary education who responded to survey items in a cross-sectional design. NA shows a two-dimensional graphical network of items (edges) and the relations between them (edges). In addition, statistical indices can be used to identify those nodes that show numerous or strong links to others or bridge clusters (communities) of nodes. The NA demonstrated that emotions and value (positive and negative) but not control cohered into distinct communities. Many, but not all, edges were in support of CVT; there were positive links between control/positive value and enjoyment and pride, and negative links for boredom, as well as negative links between negative value and enjoyment and pride, and positive links for boredom. Three control-value nodes were particularly influential: that lessons were important/valuable (positively) and that work required too much time (negatively). Interventions and classroom instructional strategies that build value/importance and reduce perceptions of time cost may be particularly effective in facilitating positive emotions and reducing negative emotions.